2000
DOI: 10.1038/labinvest.3780119
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Relationship of Macrophages and Monocyte Chemotactic and Activating Factor/Monocyte Chemoattractant Protein-1 in the Ischemic and Reperfused Rat Heart

Abstract: SUMMARY:Reperfusion injury is a troublesome and unresolved problem in acute myocardial infarction and is believed to be associated with inflammatory reactions in which various types of cells and cytokines participate, in particular, macrophages and monocyte chemoattractant protein-1 (MCP-1). We designed this study to clarify the role and relationship of macrophages and MCP-1 in ischemic and reperfused heart. The number and distribution of macrophages and MCP-1 messenger RNA (mRNA) in the ischemic and reperfuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 21 publications
2
71
0
Order By: Relevance
“…In addition to its critical role in mononuclear cell recruitment, MCP-1 exerts important actions on nonhematopoietic cells, inducing angiogenic and arteriogenic effects [122] and modulating fibroblast phenotype and activity by increasing collagen expression and by regulating MMP synthesis [123]. MCP-1 upregulation has been demonstrated in a canine [124], a rat [125,126] and a mouse model [127] of experimental myocardial infarction. Studies from our laboratory demonstrated that MCP-1 −/− mice had decreased and delayed macrophage infiltration in the healing infarct and exhibited delayed replacement of injured cardiomyocytes with granulation tissue.…”
Section: Chemokines In Myocardial Infarctionmentioning
confidence: 99%
“…In addition to its critical role in mononuclear cell recruitment, MCP-1 exerts important actions on nonhematopoietic cells, inducing angiogenic and arteriogenic effects [122] and modulating fibroblast phenotype and activity by increasing collagen expression and by regulating MMP synthesis [123]. MCP-1 upregulation has been demonstrated in a canine [124], a rat [125,126] and a mouse model [127] of experimental myocardial infarction. Studies from our laboratory demonstrated that MCP-1 −/− mice had decreased and delayed macrophage infiltration in the healing infarct and exhibited delayed replacement of injured cardiomyocytes with granulation tissue.…”
Section: Chemokines In Myocardial Infarctionmentioning
confidence: 99%
“…MCP-1 may also contribute to complications after MI, including acute reperfusion injury 26 and chronic ventricular remodeling and heart failure. 27,28 Within 1 hour after ischemia-reperfusion, MCP-1 gene expression is increased in the infarct territory.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
“…MCP-1 synthesis is upregulated in patients with dilated cardiomyopathy, 42,43 experimental models of heart failure, 44 and after experimental myocardial infarction. 45,46 Targeted expression of the MCP-1 gene in murine cardiac muscle induced marked macrophage infiltration, leading to depressed contractile function, hypertrophy, dilation, and myocardial fibrosis. 47 In addition to its potent mononuclear cell chemotactic activity, MCP-1 may directly mediate fibrosis through stimulation of fibroblast collagen and transforming growth factor-␤ expression.…”
Section: Recovering Myocardial Segments Demonstrate Mcp-1 Expression mentioning
confidence: 99%